Women farmers and agripreneurs must take action to influence global development agendas - Rowan-Campbell, Dorienne (Technical Centre for Agricultural and Rural Cooperation, 2019)
Throughout history, women have made gains in control of their selves, assets and visibility in a male dominated world, and then lost them. In those moments, like Penelope waiting for Ulysses, women unpicked and restitched the tapestry of their lives. We could be facing another of those unstitching moments right now, as women's roles and aspirations are being challenged in many arenas. It is time to recast and restitch.